2011
DOI: 10.1597/09-035
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Study of Orofacial Clefts in Hamedan City, Iran: A 15-Year Study

Abstract: The birth prevalence of CL/P in Hamedan City was closer to the prevalence of CL/P in the United States and Europe than Africa and the Far East. We found that the presence of cleft in parents, siblings, and other relatives; maternal drug intake; trauma; radiation; and smoking were risk factors for cleft development in newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 48 publications
5
24
1
5
Order By: Relevance
“…Indeed, we found a higher frequency of associated congenital malformations, whereas African studies found lower frequencies between 4 and10.5% [18, 19]. Our result, however, was lower than in some reports from the Middle East and Asia where [20] found a frequency of 43.3% in Jordan, [2] reported 14.8% in India; [3, 4] reported 17.8 and 21.6% in Iran, respectively. Furthermore, our rates of associated malformations were even lower than those reported from Europe (29–59.2%) [13, 15, 21] and Latin America (31.4–48.4%) [5, 8].…”
Section: Discussioncontrasting
confidence: 81%
“…Indeed, we found a higher frequency of associated congenital malformations, whereas African studies found lower frequencies between 4 and10.5% [18, 19]. Our result, however, was lower than in some reports from the Middle East and Asia where [20] found a frequency of 43.3% in Jordan, [2] reported 14.8% in India; [3, 4] reported 17.8 and 21.6% in Iran, respectively. Furthermore, our rates of associated malformations were even lower than those reported from Europe (29–59.2%) [13, 15, 21] and Latin America (31.4–48.4%) [5, 8].…”
Section: Discussioncontrasting
confidence: 81%
“…(6) Fonoaudióloga; Professora adjunto do Curso de Fonoaudiologia da Pontifícia Universidade Católica de Minas Gerais -PUC Minas, Belo Horizonte, MG, Brasil; Doutora em Linguística pela Universidade Federal de Minas Gerais. (7) Fonoaudióloga; Professora adjunto do Curso de Fonoaudiologia da Pontifícia Universidade Católica de Minas Gerais -PUC Minas, Belo Horizonte, MG, Brasil; Doutora em Linguística pela Universidade Federal de Minas Gerais.…”
unclassified
“…Also, a prevalence of 1.016 per 1000 live births was reported in Hamadan, which is in the northwest of Iran. 10 In Tehran, the capital of Iran, the overall incidence of CL/P between 1998 and 2005 was reported as 2.14 per 1000 live births. 11 Moreover, a prevalence of 0.97 and 0.80 per thousand live births was reported in the north and southwest of Iran, respectively.…”
Section: Discussionmentioning
confidence: 99%